The flow behavior of powder stearin-based methyl ester sulfonates and the effect of glidant - Abd Maurad, Zulina; Abdullah, Luqman Chuah; Anuar, Mohd Shamsul; Abdul Karim Shah, Nor Nadiah; Idris, Zainab (Elsevier, 2023)
The preparation and behavior of powder stearin-based methyl ester sulfonates (MES) with the addition of builder as a glidant agent was studied. MES is an anionic surfactant and its performance is equivalent to petroleum-based linear alkylbenzene sulfonates (LAS), the workhorses of the detergent industry. At the same time, zeolites or soda ash were the alternative builders for non-phosphate-based detergent. The behavior of powder MES properties was measured in terms of morphology, particle size, cohesion, caking, and compaction. Before that, these palm stearin-based MES of carbon chain 16e18 with ratios of 98:2, 80:20, and 60:40 in flakes were ground using a high shear mixer by 23,000 rpm to produce powder particles. Decreasing the particle size of MES powder can reduce the powder's cohesion, caking, and compaction. The addition of zeolite or soda ash as a glidant in powdered MES can improve the caking behavior. The high stearic in MES greatly influenced getting fine particle powders and required more glidant agents. This powder MES with excellent powder characteristics can perform well as a bio-based cleaning product.